The Philosophical Interpretation of Risk Assessment in Municipal Project Management - Tshughuryan, Armen; Barati, Reza (Տիգրան Մեծ)
Project management emphasizes the process of risk assessments, because any project is attended not only by the risks of failure due to lack of funding, but also by the design of the required quality and quantity of final results. Consequently, there is a need to show a new philosophical approach to the identification, evaluation and decision-making of the risks in programs, implemented in municipal structures, because the range of beneficiaries related to this field is not only wide, but also more multi-layered (government, municipal authorities, investors, middle-level and top managers, population, etc.). The article proposes a model of risk management of projects, implemented in municipal facilities, which enables not only to form a management information feedback between all beneficiaries, but also to include them in participatory risk prevention processes. A ranking process of risk factors related to the management of municipal projects is also proposed, which increases the effectiveness of managerial decisions, aimed at risk prevention and the justification of philosophical interpretations related to it.
Keywords: Social philosophy